Dopamine receptor D4 (DRD4) gene modulates the influence of informational masking on speech recognition. (January 2015) - Xie, Zilong; Maddox, W. Todd; Knopik, Valerie S.; McGeary, John E.; Chandrasekaran, Bharath
Abstract: Listeners vary substantially in their ability to recognize speech in noisy environments. Here we examined the role of genetic variation on individual differences in speech recognition in various noise backgrounds. Background noise typically varies in the levels of energetic masking (EM) and informational masking (IM) imposed on target speech. Relative to EM, release from IM is hypothesized to place greater demand on executive function to selectively attend to target speech while ignoring competing noises. Recent evidence suggests that the long allele variant in exon III of the DRD4 gene, primarily expressed in the prefrontal cortex, may be associated with enhanced selective attention to goal-relevant high-priority information even in the face of interference. We investigated the extent to which this polymorphism is associated with speech recognition in IM and EM conditions. In an unscreened adult sample (Experiment 1) and a larger screened replication sample (Experiment 2), we demonstrate that individuals with the DRD 4 long variant show better recognition performance in noise conditions involving significant IM, but not in EM conditions. In Experiment 2, we also obtained neuropsychological measures to assess the underlying mechanisms. Mediation analysis revealed that this listening condition-specific advantage was mediated by enhanced executive attention/working memory capacity in individuals with the long allele variant. These findings suggest that DRD4 may contribute specifically to individual differences in speech recognition ability in noise conditions that place demands on executive function. Highlights: We studied the effect of genetic variation on speech perception in noise. DRD 4 long allele carriers showed a selective advantage in informational masking. Executive attention/working memory measures mediated this selective advantage.